The effectiveness and efficiency of general international standards and archival description in the retrieval of archival materials at the University of the Philippines Diliman Archives and Records Depository - Dizon, Denisse Hope O.; Lagrama, Eimee Rhea, C. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
For years, the University of the Philippines Diliman Archives and Records Depository or UARD has been using their own devised description system for the search and retrieval materials. The mentioned description system is very general and therefore might slow down search queries and/or research processes.
The researcher found it appropriate for UARD to use General International Standard Archival Description or ISAD(G), an international standard description for archives, to evaluate whether using ISAD(G) is more effective (accuracy of answers) and more efficient (search speed) in the search and retrieval of information compared to the description system currently in use. Also, a State University using an international standard description will set an example for other universities and other archival institutions to adopt the description system that might improve search and queries and research processes.
In an experiment comprising of 10 subjects who underwent a search query test using the UARD-devised description system (condition A) and the ISAD(G) description system (condition B), the researcher measured the effectiveness of ISAD(G) description system versus the UARD-devised description system by evaluating the correctness of the answers garnered by the experiment subjects. To measure efficiency, the researcher measured the search speed of the subjects using both description systems. A question was given to the subjects and they must look for the correct answer through the archival materials using the two description systems mentioned. The search queries under both conditions were timed by the researcher.
Taking into consideration the accuracy of the subjects' answer to the question, all of them got the correct answer under Condition B while only one got the correct answer under Condition A; the subject then explaining that he/she did not completely read and fully rely on the archives finding aid under Condition A and just deliberately browsed through the selected documents after scanning the archives finding aid under condition A.
The average speed of the subjects using the UARD-devised descriptions system is 291.30 seconds or around 4 minutes 51 seconds while the average speed using the ISAD(G) description system is 102.20 seconds or just around 1 minute 42 seconds. The difference between these two averages is 189.1 seconds or 3 minutes and 9 seconds which is technically large and therefore statistically significant.
The results of the experiment showed the effectiveness and efficiency of ISAD(G) as a description standard and therefore is said to be plausible for adoption in the UARD System.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Diliman Archives and Records Depository; Information storage and retrieval systems -- Archival materials